"If you think you've got a lump, they'll screen you." Informed consent, health promotion, and breast cancer. Issue 2 (13th April 2004) - Pfeffer, N
Abstract : A great deal has been written about information that is or should be provided when seeking consent to medical research and treatment. Relatively little attention has been paid to information describing health promotion interventions. This paper critically examines some information material describing three different methods of encouraging early presentation of breast cancer in the UK: the NHS breast screening programme, breast self examination, and breast awareness. Findings from a content analysis of printed material and a series of focus group discussions that included women who speak little or no English were organised around the Department of Health's recommendations about the information which should be provided when seeking consent to treatment and research. They exposed inconsistencies, ambiguities, and gaps, which when taken together suggest both compliance and non-compliance are being achieved in the absence of informed consent. The findings also provide a starting point for a discussion about how informed consent to health promotion might be sought.